(untitled) (LEGAL DIALOGICA, 2025)
This study analyzes the Draft Law on Asset Forfeiture (RUU Perampasan Aset) in the context of combating corruption crimes in Makassar. The findings reveal that this draft law plays a strategic role in strengthening the legal framework for eradicating corruption by providing more effective legal instruments to recover state losses. The RUU facilitates and accelerates the recovery of state assets stolen by corrupt actors through a clear legal framework and harmonization with other laws. Moreover, it grants greater authority to law enforcement agencies to access financial information and suspicious transactions and allows asset confiscation without awaiting a final criminal verdict. This draft law also upholds the principle of justice by ensuring that the proceeds of crimes cannot be enjoyed by perpetrators and aligns with international standards, enhancing global cooperation. With implementation aligned with existing regulations, the RUU Perampasan Aset is expected to be a significant breakthrough in the fight against corruption in Makassar and Indonesia as a whole. Abstrak: Penelitian ini menganalisis Rancangan Undang-Undang (RUU) Perampasan Aset dalam konteks penegakan hukum tindak pidana korupsi di Makassar. Hasil analisis menunjukkan bahwa RUU ini memiliki peran strategis dalam memperkuat sistem hukum pemberantasan korupsi dengan menyediakan instrumen hukum yang lebih efektif untuk memulihkan kerugian negara. RUU ini mempermudah dan mempercepat proses pemulihan aset negara yang dicuri oleh pelaku korupsi melalui kerangka hukum yang jelas dan harmonisasi dengan undang-undang lain. Selain itu, RUU ini memberikan wewenang lebih besar kepada aparat penegak hukum untuk mengakses informasi keuangan dan transaksi mencurigakan, serta memungkinkan perampasan aset tanpa harus menunggu putusan pidana final. RUU ini juga mendukung prinsip keadilan dengan memastikan bahwa hasil kejahatan tidak dapat dinikmati oleh pelaku, serta sesuai dengan standar internasional yang meningkatkan kerja sama global. Dengan implementasi yang selaras dengan peraturan perundang-undangan yang ada, RUU Perampasan Aset diharapkan menjadi terobosan penting dalam pemberantasan korupsi di Makassar dan Indonesia secara keseluruhan.